Selenium exposure on breast cancer risk and progression: Comprehensive analysis identifies MSRB1 as a novel therapeutic target - Jingsong Cheng; Diyuan Zhang; Ningxi Wang; Ziheng Zheng; Cong Zhang; Nanting Chen; Yuanyuan Wan; Xue Chen; Qingyao Yin; Xinyi Zhu; Yu Zhao; Liming Yi; et al. (Ecotoxicology and Environmental Safety)
Background: Breast cancer (BRCA) is the most common malignancy in women worldwide. Selenium (Se), a crucial trace element, significantly impacts BRCA patient survival, although its roles in tumorigenesis, the tumor immune microenvironment (TIME), and precision therapy remain unclear. Methods: We used Mendelian randomization to investigate the causal link between blood Se and BRCA risk. Transcriptome profiling of 25 selenoproteins, combined with the TCGA-BRCA and METABRIC cohorts, identified Se-related patterns, including two Se clusters, and a Se-related risk score (SeRS) was developed via machine learning. We assessed the relationships of the SeRS with clinical features, prognosis, cancer hallmarks, stemness, the TIME, and the ICI therapy response. The CMap database identified potential BRCA drugs, while random forests pinpointed critical selenoproteins. In vitro experiments in MCF-7 and MDA-MB-231 cells explored the impact of MSRB1 on tumor characteristics and oxidative stress. Results: Our results established a protective causal link between blood Se and BRCA risk. Two Se clusters (SeC1 and SeC2) were identified on the basis of selenoprotein expression. The SeRS, which incorporates SELENOH, GPX4, GPX1, MSRB1, TXRND1, and SELENOV, strongly predicted clinical outcomes and ICI therapy response. Potential drugs to overcome chemotherapy resistance were identified. MSRB1, with the highest copy number variation (CNV) and a significant role in BRCA, was deemed the most critical selenoprotein in BRCA. Its depletion significantly reduced BRCA cell proliferation, migration, and invasion while increasing reactive oxygen species. Conclusions: This study introduces a novel selenoprotein-based classification and prognostic signature for BRCA patients, enhancing personalized prognosis and precision therapy. These findings highlight MSRB1 as a potential therapeutic target, offering new insights into the roles of Se and selenoproteins in BRCA treatment.